Assessment of current practice for β-lactam therapeutic drug monitoring in French ICUs in 2021: a nationwide cross-sectional survey. (5th September 2022) - Tritscher, Perrine; Delannoy, Matthieu; Agrinier, Nelly; Charmillon, Alexandre; Degand, Nicolas; Dellamonica, Jean; Roger, Claire; Leone, Marc; Scala-Bertola, Julien; Novy, Emmanuel
Abstract: Background: Current guidelines and literature support the use of therapeutic drug monitoring (TDM) to optimize β-lactam treatment in adult ICU patients. Objectives: To describe the current practice of β-lactam monitoring in French ICUs. Methods: A nationwide cross-sectional survey was conducted from February 2021 to July 2021 utilizing an online questionnaire that was sent as an email link to ICU specialists (one questionnaire per ICU). Results: Overall, 119 of 221 (53.8%) French ICUs participated. Eighty-seven (75%) respondents reported having access to β-lactam TDM, including 52 (59.8%) with on-site access. β-Lactam concentrations were available in 24–48 h and after 48 h for 36 (41.4%) and 26 (29.9%) respondents, respectively. Most respondents ( n =  61; 70.1%) reported not knowing whether the β-lactam concentrations in the TDM results were expressed as unbound fractions or total concentrations. The 100% unbound fraction of the β-lactam above the MIC was the most frequent pharmacokinetic and pharmacodynamic target used ( n =  62; 73.0%). Conclusions: Despite the publication of international guidelines, β-lactam TDM is not optimally used in French ICUs. The two major barriers are β-lactam TDM interpretation and the required time for results.